Electrochemical sensing of toxic gases in room temperature ionic liquids - Murugappan, Krishnan S/O (Curtin University, 2015)
This study investigates the electrochemical behaviour of three highly toxic gases, methylamine, chlorine and hydrogen chloride in room temperature ionic liquids (RTILs) on both conventional electrodes and screen printed electrodes (SPEs). It was found that all gases give good analytical responses and comparable limits of detection on both electrodes. This suggests that low-cost SPEs can be used in conjunction with RTILs for amperometric gas detection, which would allow faster response times and cheaper manufacturing costs.